FREE REPLANTATION OF TOTAL AVULSED SCALP- A CASE REPORT - Noveski, Lazo; Dzonov, Boro; Mircevska, Elizabeta; Jovanovska, Katerina; Georgieva, Gordana (Journal of Morphological Sciences, 2020)
We present the case of a 38-year-old female who came to our Clinic 5 hours after injury with scalp avulsion due to entanglement of head scarf in the motorized machine  with a good final result after which the patient can use a wig. During the treatment, hyperbaric oxygen therapy was applied, after which we had a dilemma about the benefits of using it. Key words : injury, scalp, replantation, surgery